The Potent Antimicrobial Spectrum of Patchouli: Systematic Review of Its Antifungal, Antibacterial, and Antiviral Properties - Kemala, Pati; Idroes, Rinaldi; Khairan, Khairan; Ramli, Muliadi; Tallei, Trina Ekawati; Helwani, Zuchra; Rahman, Sunarti Abd (Malacca Pharmaceutics, 2024)
ntention towards natural essential oils from medicinal plants has increased rapidly over the past decade as these oils have antimicrobial and antioxidant properties against various chronic diseases. One essential oil source with antimicrobial properties is the essential oil from Pogostemon cablin (Blanco) Benth. This review aims to provide information on using patchouli oil as an antimicrobial against bacterial, fungal, and viral pathogens in the last five years. There were 37 articles found in the PUBMED database by June 15, 2023. After searching, 6 of them were duplicates. A total of 2 papers were inaccessible, 4 were not research articles, and five were excluded because they were irrelevant to the scope of this study. This review shows that research related to patchouli as an antimicrobial in the last five years involves Pogostemon cablin leaf samples as silver nanoparticle bioreductors. Patchouli oil is used in membrane, nanocomposite film, and starch hydrogel manufacturing. Patchouli oil is a prestigious antimicrobial agent because it can fight numerous pathogenic microbes from bacteria, fungi, and viruses.